Exact Discrete Analogs of Derivatives of Integer Orders: Differences as Infinite Series. (4th November 2015) - Tarasov, Vasily E.
Abstract : New differences of integer orders, which are connected with derivatives of integer orders not approximately, are proposed. These differences are represented by infinite series. A characteristic property of the suggested differences is that its Fourier series transforms have a power-law form. We demonstrate that the proposed differences of integer orders n are directly connected with the derivatives ∂ n / ∂ x n . In contrast to the usual finite differences of integer orders, the suggested differences give the usual derivatives without approximation.